2019
DOI: 10.1002/ccd.28345
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intensively lowered low‐density lipoprotein cholesterol on deferred lesion prognosis

Abstract: Objectives The aim of this study was to investigate the impact of intensively lowered low‐density lipoprotein cholesterol (LDL‐C) level on the deferred lesion prognosis after revascularization deferral based on fractional flow reserve (FFR). Background Lowering LDL‐C is associated with lower cardiovascular event rate, but its benefit on the deferred lesion prognosis has not been well evaluated. Methods This retrospective, single‐center, observational study analyzed 192 deferred lesions with FFR value >0.80 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…All patients with intermediate coronary stenosis, which were performed FFR measurement, should be received intensive LDL-C management. In a previous study by Nakamura et al 15 , uncontrolled LDL-C levels were found to be associated with a higher risk of deferred lesion failure and any unplanned revascularization in patients with deferred lesion. Despite the well-established importance of LDL-C management in patients with CAD, our study findings suggest that there may be insufficient LDL-C management in clinical practice after FFR measurement.…”
Section: Discussionmentioning
confidence: 84%
“…All patients with intermediate coronary stenosis, which were performed FFR measurement, should be received intensive LDL-C management. In a previous study by Nakamura et al 15 , uncontrolled LDL-C levels were found to be associated with a higher risk of deferred lesion failure and any unplanned revascularization in patients with deferred lesion. Despite the well-established importance of LDL-C management in patients with CAD, our study findings suggest that there may be insufficient LDL-C management in clinical practice after FFR measurement.…”
Section: Discussionmentioning
confidence: 84%
“… 18,20,21,24 Other factors identified in those studies, which would be associated with DTLF or higher rates of more general cardiovascular events, however, cannot be confirmed here. A reason for this could be that factors such as LDL‐C values after baseline FFR have a stronger predictive value than statin use alone, and, thus, could be of additive value to risk factors identified in this study 34 …”
Section: Discussionmentioning
confidence: 92%
“…Likewise, Hakeem et al reported a DTLF event rate of 18 and 9.5%, respectively, in patients initially presenting with ACS or stable CAD after 3.4 years follow‐up 18 . In stable CAD patients, Nakamura et al reported a DTLF rate of 7.8% at 2.8 years follow‐up 34 . In ACS patients, Picchi et al reported a DTLF event rate of 9% at 2 years follow‐up.…”
Section: Discussionmentioning
confidence: 98%
“…Statin use at discharge was higher among those with LDL-C < 70 mg/dL (93.4% vs 81.7%, p = 0.032), and a similar trend toward higher statin use was seen at the time of last follow-up among those with LDL-C < 70 mg/dL (91.8% vs 80.9%, p = 0.053). Interestingly, there was a greater rate of deferred lesion failure (defined as either deferred lesion revascularization or deferred vessel MI) among those with LDL-C > 70 mg/dL [22] . In contrast to these findings we observed a loss of initial intensification of therapy over time among those with FFR > 0.8.…”
Section: Discussionmentioning
confidence: 99%